2005
DOI: 10.1523/jneurosci.1637-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Fine Depth Discrimination in Monkey Inferior Temporal Cortex

Abstract: Binocular disparity is an important visual cue that gives rise to the perception of depth. Disparity signals are widely spread across the visual cortex, but their relative role is poorly understood. Here, we addressed the correlation between the responses of disparity-selective neurons in the occipitotemporal (ventral) visual pathway and the behavioral discrimination of stereoscopic depth. We recorded activity of disparity-selective neurons in the inferior temporal cortex (IT) while monkeys were engaged in a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 36 publications
7
61
0
Order By: Relevance
“…Our microstimulation results add support for the bottom-up direction of the relationship of V4 neurons with perceptual decisions. Uka et al (2005) reported that neurons in the IT show choicepredictive activity 360 ms after stimulus onset. This is three times the latency of the visual response, or the latency of disparity selectivity (Uka et al, 2005).…”
Section: Latency Of Choice-predictive Activity During Fine Disparity mentioning
confidence: 99%
See 2 more Smart Citations
“…Our microstimulation results add support for the bottom-up direction of the relationship of V4 neurons with perceptual decisions. Uka et al (2005) reported that neurons in the IT show choicepredictive activity 360 ms after stimulus onset. This is three times the latency of the visual response, or the latency of disparity selectivity (Uka et al, 2005).…”
Section: Latency Of Choice-predictive Activity During Fine Disparity mentioning
confidence: 99%
“…Uka et al (2005) reported that neurons in the IT show choicepredictive activity 360 ms after stimulus onset. This is three times the latency of the visual response, or the latency of disparity selectivity (Uka et al, 2005). The increase in the delay of the choicepredictive activity from V4 to IT (230 ms) is disproportionate to the increase in the delay of the visual response or the disparity selectivity (ϳ20 ms) (Watanabe et al, 2002;Tanabe et al, 2004;Uka et al, 2005).…”
Section: Latency Of Choice-predictive Activity During Fine Disparity mentioning
confidence: 99%
See 1 more Smart Citation
“…These observations may reflect a causal link between the activity of single neurons and sensory decisions. Several groups quantified these correlations with choice probabilities (CPs), allowing comparison across cortical areas (Celebrini and Newsome, 1994;Britten et al, 1996;Uka et al, 2005) and visual tasks Dodd et al, 2001;Uka and DeAngelis, 2004;Purushothaman and Bradley, 2005;Uka et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…One method that has been widely used to suggest that signals from particular neurons contribute to a given perceptual decision combines threshold psychophysics with single-unit recordings. A trialto-trial correlation between neuronal activity and perceptual judgment, which cannot be explained by the visual stimulus, is taken as evidence that neuronal signals contribute to a decision [1][2][3][4][5][6][7] . Such correlation, often quantified by 'choice probability', should then also depend on the task strategy employed by the subject 6 .…”
Section: Introductionmentioning
confidence: 99%